Challenges of organic amendments: Impact of vermicompost leachate and biochar on popcorn maize in saline soil - Rivas, Brenda (2025)
Organic amendments offer a sustainable strategy to enhance soil quality in degraded environments, while also contribute to reducing greenhouse gas generation and implementing a green economy. This study evaluated the comparative effects of two organic amendments— vermicompost leachate and biochar—on the performance of Popcorn maize (Zea mays L. var. everta) grown under saline soil conditions. Four treatments were tested: T0 (Control), T1 (Vermicompost leachate), T2 (Biochar), and T3 (Vermicompost leachate + Biochar), each with 10 replicates arranged in a Completely Random Design (CRD). Although several soil physicochemical, microbiological, and agronomic parameters showed no significant differences compared to the control, biochar application led to notable improvements in soil total organic carbon, microbial community (mesophilic aerobes bacteria, molds, and yeasts), and increased seed length and diameter. In contrast, vermicompost leachate alone had a detrimental effect on plant growth, including reduced leaf area, stem thickness, and grain yield. Notably, grain yield declined by 46% with leachate alone and by 31% when combined with biochar, compared to the control. These results highlight the superior performance of biochar over vermicompost leachate as a soil amendment under saline conditions and underscore the potential risks of broadly applying compost teas in stressed soils. Site-specific assessments and screening for phytotoxins and phytopathogens are recommended before use. Furthermore, the combined use of leachate and biochar may not be advisable under the tested soil characteristics.